(untitled) (BULLETIN OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV. ORIENTAL LANGUAGES AND LITERATURES, 2025)
B a c k g r o u n d. An important aspect of studying intercultural phenomena is comparative research in the field of literary studies. Particular attention should be paid to periods in national literatures when questions of national and personal existence become especially acute. Such a period was the «literary thaw» − in Ukraine during the 1960s and in China during the 1980s. Lina Kostenko and Shu Ting are prominent representatives of the poetry of the «thaw» period, whose work reflects the thematic dominants and aesthetic principles of modernism. A significant and illustrative element of both poets’ work is the reinterpretation of mythological motifs in order to endow contemporary issues with archetypal and symbolic depth. Therefore, a comparative study of the poetry of Shu Ting and Lina Kostenko is highly relevant, as it enables an understanding of the commonalities and differences in how the Chinese and Ukrainian poets approach the eternal questions of human existence, national memory, and identity. M e t h o d s. A number of methods were employed in the course of this study. The methods of cultural-historical and philological analysis made it possible to identify the foundations and specific features of the artistic phenomenon of the «literary thaw». The method of commentary enabled the determination of the primary meanings of mythological images and motifs, while the interpretive method allowed for an analysis of their innovative reinterpretation in the poetry of Shu Ting and Lina Kostenko. The comparative method was applied to identify commonalities and differences in the contemporary reinterpretation of mythological motifs in the poets’ works. R e s u l t s. The analysis of the poetry of Lina Kostenko and Shu Ting revealed that both poets actively reinterpret mythological motifs and images to express their individual worldviews. Shu Ting predominantly turns to gynocentric mythology, featuring strong, wise, and talented goddesses. In constructing the image of the modern woman, Shu Ting incorporates motifs of «pure beauty», «ideal femininity», and «sacred naturalness», combined with motifs of «personal freedom», «struggle», and others. Lina Kostenko also reinterprets the image of the modern woman, but places emphasis on mythological motifs of «outer and inner beauty» and the «struggle between good and evil in the nature of woman», within the context of contemporary challenges. The uniqueness of Lina Kostenko’s poetry lies in her reinterpretation of mythological motifs related to historical and political themes, such as «struggle/grandeur», «oblivion/loss», «love for the homeland», and others. C o n c l u s i o n s. In conclusion, the reinterpretation of mythological motifs can be regarded as an international instrument of modernist reflection on reality. However, the focus of employing this instrument within the framework of the «literary thaw» depends on the overarching thematic concerns of the authors’ work, particularly the correlation between the individual and national dimensions.